Effect of inlet boundary conditions on computational fluid dynamics (cfd) simulations of gas-solid flows in risers - Shah, Milinkumar; Utikar, Ranjeet; Evans, G.; Tade, Moses; Pareek, Vishnu (American Chemical Society, 2012)
The effect of type of inlet conditions on the predictions of EulerianEulerian simulations of a circulating fluidized bed riser has been investigated in both 2D and 3D domains. The 2D simulations were conducted using 3 different inlet configurations: (A) solids entering in radial direction from a two-sided inlet and gas entering axially from the bottom inlet, (B) solid entering axially from a two-sided bottom inlet near the wall and gas entering axially from a bottom inlet at the center, and (C) gas phase entering axially from a two-sided bottom inlet near the wall and solids entering axially from a bottom inlet at the center. In 2D simulations, it was found that both time-averaged axial velocity and solids volume fraction radial profiles were functions of the inlet kinetic energy as well as gas solidmixingpatterns at the inlet. Whereas 2D simulations using boundary conditions A and C showed significant deviations from experimental profiles, the boundary condition B as well as full-scale 3D simulations gave reasonable agreements with experimental observations.